Analisis Ekonomi Politik Keynesian Menuju Indonesia Emas - Ningrum, Indi Juniartri Cahya; Saepudin, Eli Apud; Triyana, Reza; Nurfaridah, Aninda; Putri, Dian Maharani; Dewi, Rani Anggreini (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Objective to analyze the potential of Keynesian Political Economy in helping Indonesia achieve the Golden Indonesia Vision 2045. Methods Literature review and descriptive analysis of the Keynesian Political Economy framework and its relevance to the Indonesian context. Results Keynesian Political Economy offers a useful framework to achieve a Golden Indonesia 2045 through fiscal and monetary policy increasing government spending and lowering interest rates to boost economic growth. Government intervention implementing progressive tax and minimum wage to achieve equitable income distribution. Policy implementation effectiveness challenges. Market distortions and inefficiencies. Fiscal balance. Conclusion Keynesian Political Economy can help Indonesia achieve the Golden Indonesia 2045, but requires careful and contextual implementation.